Confidence and performance of health workers in cardiovascular risk factor management in rural Botswana: a cross-sectional study. (March 2019) - Gala, Pooja; Seth, Bhavna; Moshokgo, Veronica; M'buse, Rudy; Kazadi, Emmanuel; Pharithi, Solomon; Gobotsamang, Kabelo; Dintwe, Keolebogile; Olyn, Ruth Kesolofetse; Lewis, Brett; Kalenga, Kitenge; Tapela, Neo; et al.
Abstract: Background: Social and demographic changes in Botswana are resulting in an increased prevalence of cardiovascular disease (CVD). Providers, mostly nurses, in this setting have limited training in managing CVD risk and few opportunities for continued medical education. We aimed to evaluate providers' perceived confidence in managing CVD risk factors and describe management of patients with hypertension at public-sector clinics in a rural district of Botswana. Methods: In this cross-sectional study, we invited public-sector health-care providers in 11 ambulatory clinics in the Kweneng East district of Botswana to complete an anonymous questionnaire survey. We used descriptive statistics to evaluate providers' confidence in managing CVD risk (a Likert scale from 1 [low confidence] to 5 [high confidence]). We used t tests to compare confidence levels between groups of providers and specific risk factors. Additionally, we interviewed patients and did chart reviews to assess how CVD risk factors were managed in 275 hypertensive patients at seven of the 11 sites surveyed. Uncontrolled hypertension was defined as ≥140/90 mm Hg (or ≥130/80 mm Hg in patients with diabetes) for an average of two blood pressure readings and CVD risk was defined using WHO guidelines. Findings: Of 88 health care providers invited to participate, 44 registered nurses (80%), four family nurse practitioners (7%), and seven doctors (13%) completed the survey. Providers reported feeling significantly more comfortable managing hypertension than they did diabetes (3·73 vs 3·15; p<0·0001) and had lowest confidence with a mean Likert rating of 1·95 (95% CI 1·58–2·31), 2·27 (95% CI 1·93–2·62), and 2·13 (95% CI 1·75–2·51) for prescribing aspirin, statins, and adjusting insulin, respectively. Of the 275 patients with hypertension, 55% (152) had uncontrolled hypertension, and 45% (69) of those with uncontrolled hypertension had no changes to their medications over the course of a year. Of 53 patients who also had diabetes, 51% (27) had uncontrolled disease and an additional 15% (8) had no recent blood glucose check. Of 52 patients with 10-year CVD risk of more than 10%, 55·7% (29) were prescribed aspirin and 15% (8) a statin. Interpretation: Public sector health-care providers in rural Botswana have low confidence in managing CVD risk factors. Although reported confidence was higher for management of hypertension than for diabetes, there were significant lapses in management of both diseases. CVD and diabetes account for 22% of all adult deaths in Botswana and it is imperative that training in management of these diseases is improved. To address low provider confidence and gaps in guideline-driven CVD prevention, we plan to implement an integrative training programme for health workers in the Kweneng East district of Botswana. Funding: Hospital Medicine, Beth Israel Deaconess Medical Center.